Особливості країн-лідерів рейтингів сталого розвитку - Іщенко, О.В. (Вісник економічної науки України, 2014)
На основі результатів досліджень Світового центру даних з геоінформатики та сталого розвитку при НТУУ "КПІ" визначено країни, які найбільш успішно реалізують принципи концепції сталого розвитку. Розглянуто специфічні особливості зазначених країн та їх ротацію у рейтингу сталого розвитку в 2007-2013 рр. На основе результатов исследований Мирового центра данных по геоинформатике и устойчивому развитию при НТУУ "КПИ" определены страны, которые наиболее успешно реализовывают принципы концепции устойчивого развития. Рассмотрены специфические особенности указанных стран и их ротация в рейтинге устойчивого развития в 2007-2013 гг. The article presents results of analysis of the achievements in the implementation of principles of sustainable development. The state of implementation of the concept of sustainable development in the world and the main factors that disturb it on the level as the international community so individual countries is considered. It is defined that there isn’t universally accepted system of indicators and methodology for assessing the achievements of countries towards the realization of the concept of sustainable development in the modern time. One of the most complex methodology is the methodology which proposed by the World Data Center for Geoinformatics and Sustainable Development (WDC-Ukraine) at NTUU "KPI". Based on the results of this research center it was found that today the most successfully and effectively implement the principles of sustainable development such countries as Australia, Austria, United Kingdom, Denmark, Ireland, Iceland , Luxembourg , New Zealand, Norway, USA, Finland, Switzerland, Sweden. It is defined that specific features of the leading of sustainable development countries are: a high level of development and competitiveness, membership in the Organization for Economic Cooperation and Development (OECD). The dynamics of the integral index of sustainable development and its components for the leading countries during years 2007-2013 is considered. The relations between the position of the country in the ranking of sustainable development and the values of the integral index of sustainable development and its components are analyzed. It is defined that during years 2007-2013 there was an increase of the integral index of sustainable development, but the multidirectional volatile dynamics of its components in the most leading of sustainable development countries. It is defined that leading of sustainable development countries can be divided into specific groups, each of which has its own particular dynamics of the integral indicator of sustainable development and its components.It is determined that positive trends of the integral indicator of sustainable development and, as a consequence, the same dynamics in the ranking of sustainable development are distinctive features for Sweden, Norway, Switzerland, Denmark, Ireland, United Kingdom, New Zealand, USA, negative - Finland, Iceland, Luxembourg, Canada, Australia.